2008
DOI: 10.1161/circresaha.108.172189
|View full text |Cite
|
Sign up to set email alerts
|

The del22q11.2 Candidate Gene Tbx1 Controls Regional Outflow Tract Identity and Coronary Artery Patterning

Abstract: Abstract-TBX1, encoding a T-box containing transcription factor, is the major candidate gene for del22q11.2 or DiGeorge syndrome, characterized by craniofacial and cardiovascular defects including tetralogy of Fallot and common arterial trunk. Mice lacking Tbx1 have severe defects in the development of pharyngeal derivatives including cardiac progenitor cells of the second heart field that contribute to the arterial pole of the heart. The outflow tract of Tbx1 mutant embryos is short and narrow resulting in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
133
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 42 publications
16
133
0
Order By: Relevance
“…4A; Sema3c-lacZ) showed X-gal staining in the OFT/subpulmonary myocardium and right ventricle, as well as in the neural tube, somites, and limb buds (Fig. 4B-E), consistent with the endogenous expression pattern of Sema3c (9,24,31,32). At E11.5, lacZ expression in the cardiovascular system, including the OFT region, was abolished in four of four independent transgenic embryos harboring the transgene with the Site1 mutation ( Fig.…”
Section: Gata6 Directly Regulates Sema3c and Plxna2 Through A Consenssupporting
confidence: 64%
See 2 more Smart Citations
“…4A; Sema3c-lacZ) showed X-gal staining in the OFT/subpulmonary myocardium and right ventricle, as well as in the neural tube, somites, and limb buds (Fig. 4B-E), consistent with the endogenous expression pattern of Sema3c (9,24,31,32). At E11.5, lacZ expression in the cardiovascular system, including the OFT region, was abolished in four of four independent transgenic embryos harboring the transgene with the Site1 mutation ( Fig.…”
Section: Gata6 Directly Regulates Sema3c and Plxna2 Through A Consenssupporting
confidence: 64%
“…To date, no molecular link has been demonstrated between GATA6 and TBX1. Interestingly, a recent study showed that the expression of Sema3c in the OFT was downregulated in mouse embryos deficient for Tbx1 (31), suggesting that GATA6 may share, at least in part, a common molecular pathway with TBX1 during OFT development (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Commonly, the clinical phenotype of individuals with GATA6 mutations involves the OFT, but is distinct from that of DiGeorge/22q11.2 deletion syndrome and, rather, manifests as non-syndromic CHD. To date, no molecular link has been demonstrated between GATA6 and TBX1, 8,9 however, a recent study showed that the expression of Sema3c in the OFT was downregulated in mouse embryos deficient for Tbx1, 10 suggesting that GATA6 may share, at least in part, a common molecular pathway with TBX1 during OFT development.…”
mentioning
confidence: 99%
“…Among the last myocardial derivatives of the SHF to be added to the elongating heart tube is future subpulmonary myocardium, a cell population specifically affected in Tbx1 mutant embryos [13]. Asymmetric addition of SHF progenitor cells giving rise to subpulmonary myocardium continues on the left side of the outflow tract up until embryonic day 12.5 in the mouse; furthermore, this late contribution drives rotation of the outflow tract, positioning subpulmonary myocardium on the ventral side of the heart and aligning the ascending aorta with the left ventricle [14].…”
Section: New Insights Into the Role And Regulation Of Noncanonical Wnmentioning
confidence: 99%